HUBUNGAN TINGKAT KECEMASAN DENGAN KETEPATAN SHOOTING THREE POINT BOLABASKET - Djawas, Aldiansyah Pratama (Jurnal Kesehatan Olahraga, 2019)
AbstractShooting three points in the sport of basketball is very often done because the highest resulting score, anxiety is one condition that affects the precision of shooting three points. This study aims to determine the relationship between the level of anxiety with the accuracy of shooting three points at high school basketball athlete Mojoagung by using the subject of research a number of 12 people.The type of research used in this study is the correlation using quantitative descriptive approach. The design used in this study is correlation with causal relationship, design that connects between two variables. The instrument used two instruments, a skill level questionnaire (SCAT) and a three point shooting accuracy testThe results of this research data managed by using SPSS program version 22.0 and manual. The results of the anxiety test have a maximum value of 8, an average of 5.1, a minimum of 3, and a standard deviation of 1.6 while a three point shooting test shows a minimum value of 13, a maximum of 25, an average of 19.5 and a standard deviation of 4 The results were calculated using SPSS and the manual count results between the two variables showed -0.663 while the sign (-) showed that the opposite relationship, ie there is a relationship between the level of anxiety with the precision of shooting three points that caused less precisely shooting three points. As for the level of relationship level of anxiety with the success of shooting three points by 44%. It can be concluded that there is a relationship between the level of anxiety with the precision of shooting three points on the athlete of SMA N Mojoagung with the correlation value of -0.663 and the greatness of the relationship with the accuracy of shooting three point 44%.Keywords: Basketball,  Shooting Three Points, Level of Anxiety .